Hubungan Sumber Daya dan Komunikasi Terhadap Implementasi Program Keluarga Harapan di Kecamatan Watukumpul Kabupaten Pemalang - Bulya Firjaun AF; Fathurrohman Fathurrohman; Dyah Lituhayu (Journal of Public Policy and Management Review, 2015)
Each policy have purpose to solve existing problems that exist in society. The implementation of a policy, there are several factors as a determinant of the success of policy, one factor of them is available resources. The resources have an important role because a policy can’t be effective if the resources that they are not available. Another factor that may affect the implementation of a policy is communication. Good communication can support the successful implementation of policy. The purpose of this research is to know how great the correlation between resources and communication for Program Keluarga Harapan (PKH) implementation. The kind of this research was a quantitative and the respondents are associated to PKH implementation in Watukumpul sub-district. The method of collecting data in this research are questionnaires. Data analysis technique that used to answer the puspose of this research is multiple correlation coefficient. Based on the results of research, known that the available resources include in good categories. Correlation test showed that the resources have positive correlation with PKH implementation. The resources and communication together have significant correlation with PKH implementation.